Pemberdayaan Kader Pemuda sebagai Agen Promosi Kesehatan Mulut melalui Edukasi Berbasis Gamifikasi - Hayyu Failasufa; Noor Rimawati; MD Irfani; Arina Najma Azizati; Erdianto Setya Wardhana (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to improve youth health cadres' knowledge and practical skills in oral health promotion through gamification-based education while strengthening their capacity as health education agents within the school environment. The program employed a training-based educational intervention using a one-group pre-experimental pre-test–post-test design involving 50 members of the Youth Red Cross (Palang Merah Remaja [PMR]) at a senior high school. The activities integrated interactive lectures, the Smile Guard Quiz gamified educational video, and hands-on simulation sessions using dental phantom models. The results demonstrated a significant improvement in participants' knowledge, with the mean score increasing from 51.7 to 80.7, representing a 56.1% increase (p < 0.001). Furthermore, 80% of participants achieved good to excellent practical skill levels, 85% demonstrated active participation throughout the program, and the mean satisfaction score reached 3.5 out of 4. These findings suggest that gamification-based oral health education is associated with improved knowledge and the development of strong practical skills among youth health cadres. This interactive educational approach has the potential to support school- and community-based oral health promotion programs.